Comparison of permanent left ventricular and biventricular pacing in patients with heart failure and chronic atrial fibrillation: prospective haemodynamic study. Issue 6 (1st June 2002) - Garrigue, S; Bordachar, P; Reuter, S; Jaïs, P; Kobeissi, A; Gaggini, G; Haïssaguerre, M; Clementy, J
Abstract : Objective: To compare clinical and haemodynamic variables between left ventricular and biventricular pacing in patients with severe heart failure; and to analyse haemodynamic changes during daily life and maximum exercise during chronic left ventricular and biventricular pacing. Design: Prospective single blinded randomised study with crossover. Setting: University hospital (tertiary referral centre). Patients and methods: 13 patients (mean (SD) age, 62 (6) years) with chronic atrial fibrillation, severe heart failure (mean ejection fraction 24 (8)%), and QRS prolongation of ≥ 140 ms had His bundle ablation and installation of a pacemaker providing left ventricular and biventricular pacing. The pacemaker was equipped with a peak endocardial acceleration (PEA) sensor. The PEA pattern was used as a haemodynamic marker during exercise as it is highly correlated with left ventricular dP/dt. After a baseline period of right ventricular pacing, all patients had two months of left ventricular pacing and two months of biventricular pacing in random order. At the end of each phase, an echocardiogram, a haemodynamic analysis at rest and on exercise during a six minute walk test, and a cardiopulmonary exercise test were performed. Results: PEA values were higher with left ventricular pacing (0.58 (0.38) m/s) and biventricular pacing (0.62 (0.24) m/s) than at baseline (0.49 (0.18) m/s) (p < 0.05). The six minute walk test showed similar performance in both pacing modes, but patients had more symptoms with left ventricular pacing at the end of the test (p = 0.035). On cardiopulmonary exercise testing, there was a greater increase in mean percentage variation of PEA with biventricular pacing than with left ventricular pacing (125 (18)% v 97 (36)%, respectively; p = 0.048) and better performance figures (92 (34) W v 77 (23) W; p = 0.03). Conclusions: During symptom limited and daily life exercise tests, chronic biventricular pacing provides better haemodynamic performance than left ventricular pacing. In heart failure patients with wide QRS complexes, the interventricular dyssynchronisation induced by left ventricular pacing may impair myocardial function during exercise.